Implementasi Terapi Murottal untuk Mengurangi Kecemasan Pasien Pre-Operasi - Hamka, Rasyid; Jerau, Emiliani Elsi; Setyawan, Martyarini Budi (Yayasan Inspirasi El Burhani, 2025)
Introduction: Preoperative anxiety is a common condition, with reported prevalence ranging from 60% to 90%. Such anxiety can affect intra-anesthetic processes, influencing biological, psychological, social, and spiritual aspects. It may lead to increased blood pressure, elevated heart rate, and bleeding. Moreover, high levels of preoperative anxiety have been shown to correlate with a greater need for postoperative analgesics. Pre-anesthesia plays a crucial role in determining surgical outcomes; therefore, non-pharmacological preoperative management is essential. One such approach is Qur’anic murottal therapy, which has been shown to be effective in reducing anxiety. Objective: This intervention was intended to lower the level of preoperative anxiety among patients at RSUD dr. Soedirman Kebumen. Method: This service program was executed by the implementer assessed participants’ anxiety levels before and after listening to the murottal therapy using the APAIS questionnaire, with a total of 30 participants selected based on predetermined criteria. Result: The average anxiety level before receiving murottal therapy was 15.03 (pre-test), which decreased to 10.8 after the intervention (post-test). As a result of this community service activity, the majority of participants (23 individuals, 76.67%) experienced moderate levels of anxiety prior to the therapy, and this figure significantly declined to only 8 individuals following the administration of murottal therapy. Conclusion: Murottal therapy was found to reduce preoperative anxiety levels among patients at RSUD dr. Soedirman Kebumen.